Healthcare providers' perceived barriers to providing breastfeeding support in Northwest rural China - Jiao-jiao Wu; Qing-ning Zhang; Su-su Liao; Jiang-hong Li; Jian-duan Zhang; Jing-zhi Huang (BMC, 2024)
Abstract Background Healthcare providers play important roles in supporting breastfeeding. Although there has been insufficient actual breastfeeding support from healthcare providers in China, little research has been conducted to understand Chinese healthcare providers' perceived barriers to providing breastfeeding support, especially in rural China. This study aims to identify these perceived barriers to providing breastfeeding support in Northwestern rural China. Methods This study was conducted during the period from March 2018 to December 2018. Forty-one healthcare providers were recruited through purposive sampling in two rural counties in Northwest China that are in close proximity to each other and share similar demographic features. Participants included obstetrician-gynecologists, midwives, nurses, "village doctors", and township and village maternal and child health workers. Qualitative data were collected through one-on-one in-depth semi-structured interviews and focus group discussions. Transcripts were thematically analyzed. Results Analysis of interview data resulted in four themes that the participants perceived as barriers to supporting breastfeeding: (1) lack of medical resources, within which inadequate staffing, and lack of financial incentives were discussed, (2) lack of clear and specific responsibility assignment, within which no one takes the lead, and mutual buck-passing were discussed, (3) healthcare providers' lack of relevant expertise, within which lack of knowledge and skills, and low prestige of village healthcare providers were discussed, (4) difficulties in accessing mothers, within which medical equipment shortages reduce services utilization, mothers' housing situation, mothers' mobility, and cultural barriers were discussed. Conclusions The study identified HCPs perceived barriers to providing breastfeeding support. Unique to China's Tri-Level Healthcare System, challenges like staffing and financial incentives are hard to swiftly tackle. Recommendations include mHealth enhancement and clarified responsibilities with incentives and tailored training. Further research is crucial to evaluate these strategies in rural Northwestern China and comparable underdeveloped areas nationwide.